Fostering Social Connectedness in First Year Seminar Students: A Pilot Study - Rebecca Kudrna; Suzanne Tiemann; Michael Swoboda; Timothy Hanrahan (Park University, 2024)
University First Year Seminar (FYS) programs are diverse in their content and pedagogy. Yet all seek to assist first-year students in the difficult college transition. The purpose of this pilot study was to evaluate if grouping similar academic majors into the existing First Year Seminar (FYS) courses would improve social connectedness, use of academic resources, and engagement on campus. A subset of first year students were assigned to either the control group (CON) of normal mixed major sections, or to the experimental course (EXP) with only related majors. Thirteen EXP and 36 CON students completed the data collection, including an 18-question social support survey administered at the beginning and end of the course. Additionally, two open-ended qualitative analysis questions were asked related to student expectations and perceived course outcomes. Lastly, the three instructors of the EXP and CON courses studied were interviewed using phenomenological methods approximately one week after the end of the semester. Between-groups analysis of the 18 quantitative survey questions identified that the CON group reported more personal conversations with peers and attendance of campus activities while the EXP group reported more faculty interactions. At the beginning of the course, 77% of the EXP group expected to create social connections as a primary course outcome, while only 19% of the CON group did. Academic skills were a higher expectation among the CON group than the EXP group. When asked more directly, both groups expected to make social connections in the class (86%). However, by the end of the study, the reported outcomes were equivocal. Interviews with FYS professors uncovered their own valuable perceptions of connectedness to the university and recommendations for instructor support were made.